How does digital leadership boost competitive performance? The role of digital culture, affective commitment, and strategic agility - Md Alamgir Mollah; Ibrahim; Abdullah Al Masud; Md Sohel Chowdhury (Heliyon)
In the age of the digital revolution, businesses are working to become more sustainable. Specifically, when management settings change—which is closely tied to competitive performance—leadership is evolving into digital leadership. Drawing on the resource-based view (RBV) theory, this study focused on finding the interconnection between digital leadership (DL) and competitive performance (CP), as well as the mediating roles of affective commitment (AC) and digital culture (DC), including the moderating effects of strategic agility (SA).To find the results of the investigation, a total 233 sample data points were gathered from employees working in manufacturing and service organizations. The research hypotheses were tested using path analysis with the AMOS-24 program. The findings indicated that DL had no direct impact on CP. While digital culture has no mediation effect but affective commitment has a full mediation effect on the relationship between DL and CP, it also found that SA hasn't played any reinforcing role in the connection between DL and CP. This study contributes to the literature on affective commitment by stressing the role of digital leaders, DC, and AC in predicting long-term CP. In addition, this study adds value to the existing literature on dynamic capabilities and RBV theory by providing evidence for the role of DL in CP. As leadership leads, dynamic capabilities can play a crucial role in managing changing culture, affective commitment, and strategic thinking for CP in Bangladesh.